Application of sorting and next generation sequencing to study 5΄-UTR influence on translation efficiency in Escherichia coli. Issue 6 (28th November 2016) - Evfratov, Sergey A.; Osterman, Ilya A.; Komarova, Ekaterina S.; Pogorelskaya, Alexandra M.; Rubtsova, Maria P.; Zatsepin, Timofei S.; Semashko, Tatiana A.; Kostryukova, Elena S.; Mironov, Andrey A.; Burnaev, Evgeny; Krymova, Ekaterina; Gelfand, Mikhail S.; et al.
Abstract: Yield of protein per translated mRNA may vary by four orders of magnitude. Many studies analyzed the influence of mRNA features on the translation yield. However, a detailed understanding of how mRNA sequence determines its propensity to be translated is still missing. Here, we constructed a set of reporter plasmid libraries encoding CER fluorescent protein preceded by randomized 5΄ untranslated regions (5΄-UTR) and Red fluorescent protein (RFP) used as an internal control. Each library was transformed into Escherchia coli cells, separated by efficiency of CER mRNA translation by a cell sorter and subjected to next generation sequencing. We tested efficiency of translation of the CER gene preceded by each of 48 natural 5΄-UTR sequences and introduced random and designed mutations into natural and artificially selected 5΄-UTRs. Several distinct properties could be ascribed to a group of 5΄-UTRs most efficient in translation. In addition to known ones, several previously unrecognized features that contribute to the translation enhancement were found, such as low proportion of cytidine residues, multiple SD sequences and AG repeats. The latter could be identified as translation enhancer, albeit less efficient than SD sequence in several natural 5΄-UTRs.